New ways of doing politics: Popular housewives - Blondet, Cecilia (1985)
In the following pages we will make some comments about the popular kitchens and their political potential as a women's organization of popular housewives and as a common space for democratic learning to the extent that their practice generates new horizontal relationships among their members. We will not develop the theme of dining rooms, nor will we show how they work or the multiple varieties that exist. We are particularly interested in beginning to answer a very general question: Why, in the 1980s, did popular housewives begin to create women's organizations in which their domestic work was legitimized, recognition of their contribution to the family economy was demanded, and they faced from there, as a public instance of collective action to other institutions of society?